ANALISIS PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING TERHADAP MATA KULIAH ILMU BAHAN BANGUNAN - Naura Salsabilla (Jurnal Salome : Multidisipliner Keilmuan, 2024)
By using the Student Centered Learning (SCL) approach, the "Freedom to Learn" curriculum is an effective curriculum that requires students to become subjects who have the potential to explore their abilities and knowledge so that they can become more active, creative, and independent in learning activities. Therefore, especially in the Building Materials Science course, teachers must be able to choose the most effective learning techniques in order to motivate students to learn more actively, creatively, and independently. In the project-based learning paradigm, students actively participate in the creation of a project or final product that is appropriate to their level of ability. This study aims to assess the impact of project-based learning strategies on Building Materials Science courses in building construction vocational education. The research technique conducted by the author is to conduct a literature study, focusing on reading and reviewing several journals and articles related to the author's topic. Through detailed analysis of several related papers and articles, this report identifies the good and bad impacts of PjBL on the Building Materials Science course, providing insights for educators and researchers in assessing successful learning models.